Enhanced Photocatalytic Performance of Nitrogen-Doped TiO2 Nanotube Arrays Using a Simple Annealing Process - Phuoc Huu Le; Le Trung Hieu; Tu-Ngoc Lam; Nguyen Thi Nhat Hang; Nguyen Van Truong; Le Thi Cam Tuyen; Pham Thanh Phong; Jihperng Leu (Micromachines, 2018)
Nitrogen-doped TiO2 nanotube arrays (N-TNAs) were successfully fabricated by a simple thermal annealing process in ambient N2 gas at 450 °C for 3 h. TNAs with modified morphologies were prepared by a two-step anodization using an aqueous NH4F/ethylene glycol solution. The N-doping concentration (0–9.47 at %) can be varied by controlling N2 gas flow rates between 0 and 500 cc/min during the annealing process. Photocatalytic performance of as-prepared TNAs and N-TNAs was studied by monitoring the methylene blue degradation under visible light (λ ≥ 400 nm) illumination at 120 mW·cm−2. N-TNAs exhibited appreciably enhanced photocatalytic activity as compared to TNAs. The reaction rate constant for N-TNAs (9.47 at % N) reached 0.26 h−1, which was a 125% improvement over that of TNAs (0.115 h−1). The significant enhanced photocatalytic activity of N-TNAs over TNAs is attributed to the synergistic effects of (1) a reduced band gap associated with the introduction of N-doping states to serve as carrier reservoir, and (2) a reduced electron‒hole recombination rate.